High rate large dynamic range analog circuitry and digitizers for fast calorimetry - Hallgren, B; Bal, F; Barr, G; Buchholz, P; Formenti, F; Funk, W; Kozhevnikov, Y; Lacourt, A; Laverriere, G; Martini, M; Papi, A; Ponting, P; et al. (IEEE, 1996)
This paper describes the issues encountered in the design of a large dynamic range digitizer for calorimetry. A gain switching technology developed for the liquid krypton calorimeter of the NA48 CP-violation experiment at CERN is described in detail. 14 bit dynamic range and better than 300 ps time resolution were achieved in beam tests with an 8 channel prototype. A mixed analog/digital ASIC has been developed. A 13'500 channel system is being produced which will be put into operation in 1996.